Structural Analysis of Katoba Ritual Text Speech in Muna Communities - S. Sarmadan; Siti Gomo Attas (Universitas Sembilanbelas November Kolaka, 2019)
The katoba ritual as a form of oral tradition from the Muna tribe is an integral part of the culture of the supporting community. The purpose of this study is to describe the structure of the ritual text speech of the Muna communities. The structure of the ritual speech utterances in this study is called the pogau toba text (PTT). This study uses a qualitative method with a Van Dijk structural approach that focuses on three frameworks of text structure, namely macro structure, superstructure, and microstructure. The results showed that 1) the macro structure, which is the overall meaning, global meaning, or general meaning of the PTT. The macro structure found in the PTT is the inauguration of a child as a Muslim. This is reflected in the pronunciation of the two words of the shahada of Asyhadu Allah ilaha Ilallah wa ashadu anna Muhammadar Rasulullah which marks a person's Islamic status; 2) superstructure, namely the four main flow structure of PTT in the context of the katoba ritual, namely opening “pembukaan”, toba conditions “syarat-syarat toba”, core of toba “inti toba”, and the closing “penutup”; and 3) microstructure, which is limited to the style of the PTT language, namely diction or choice of words in the katoba ritual emphasizing religious and moral elements that are concrete through the use of polite and gentle language, found also a parallelism in grammatical structure, and expressions metaphorical expressions that take the symbols of flora and fauna or other natural objects are presented to convey an idea, concept, or specific purpose.